2013
DOI: 10.1038/srep02948
|View full text |Cite
|
Sign up to set email alerts
|

Palladium nanoparticles deposited on silanized halloysite nanotubes: synthesis, characterization and enhanced catalytic property

Abstract: Palladium (Pd) nanoparticles were deposited on the surface of halloysite nanotubes (HNTs) modified with γ-aminopropyltriethoxysilane (APTES) to produce Pd/NH2-HNTs nanocomposites. The results indicated that Pd nanoparticles were densely immobilized onto NH2-HNTs with an average diameter of ~ 3 nm. The Pd distribution on the surface of silanized HNTs showed much more uniform, and the Pd nanoparticle size became smaller compared with those directly deposited onto HNTs without silanization. Systematic characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
117
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(134 citation statements)
references
References 38 publications
13
117
0
Order By: Relevance
“…These results reveal the presence of metallic (i.e., Pd 0 with Pd 3d 5/2 at 334.5 eV and Pd 3d 3/2 at 339.8 eV), as well as oxidic (i.e., Pd 2+ with Pd 3d 5/2 at 336.9 eV and Pd 3d 3/2 at 341.9 eV) Pd states. 35 Ag was also found to be in both metallic (i.e., Ag 0 with Ag 3d 5/2 366.8 eV and Ag 3d 3/2 372.8 eV) and oxidic (i.e., Ag + with Ag 3d 5/2 366.5 eV; Ag 3d 3/2 372.9 eV) states. 36 On the other hand, Mn was found to exist in the form of Mn 2+ (Mn 2p 3/2 at 640.3 eV), Mn 3+ (Mn 2p 3/2 at 641.6 eV) and Mn 4+ (Mn 2p 3/2 at 642.8 eV) 37,38 exhibiting an additional high-binding energy shakeup peak feature at 645.5 eV.…”
Section: +mentioning
confidence: 99%
“…These results reveal the presence of metallic (i.e., Pd 0 with Pd 3d 5/2 at 334.5 eV and Pd 3d 3/2 at 339.8 eV), as well as oxidic (i.e., Pd 2+ with Pd 3d 5/2 at 336.9 eV and Pd 3d 3/2 at 341.9 eV) Pd states. 35 Ag was also found to be in both metallic (i.e., Ag 0 with Ag 3d 5/2 366.8 eV and Ag 3d 3/2 372.8 eV) and oxidic (i.e., Ag + with Ag 3d 5/2 366.5 eV; Ag 3d 3/2 372.9 eV) states. 36 On the other hand, Mn was found to exist in the form of Mn 2+ (Mn 2p 3/2 at 640.3 eV), Mn 3+ (Mn 2p 3/2 at 641.6 eV) and Mn 4+ (Mn 2p 3/2 at 642.8 eV) 37,38 exhibiting an additional high-binding energy shakeup peak feature at 645.5 eV.…”
Section: +mentioning
confidence: 99%
“…Significant attention has been focused on the application of halloysite into many fields in these years, such as the applications in chemically blocked and controlled release [16][17][18][19][20][21], biomimetic nanoreactors [22][23][24], medicine carrier and biological antibacterial materials [25][26][27], catalysis supports [28][29][30][31][32], hydrogen storage matrix [33][34][35], food packaging applications [36], mineral templates and other functional materials [37][38][39]. Many reviews have summarized the characters and application fields of Hal minerals [40,41], for example, Yuan et al [42] introduced the main structural features and properties of halloysite, especially focused on the structure and morphology of halloysite and its changes, the formation mechanism of tubular structures, the physico-chemical properties, chemical modification of surfaces, and halloysite-based advanced materials.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Yang et al reported palladium NPs deposited on HNTs for hydrogenation of styrene with enhanced catalytic activity. 20 Recently, we reported the synthesis of novel palladium-based catalytic systems using halloysite nanotubes modied with imidazolium or triazolium moieties as supports for PdNPs and we successfully employed these supported catalysts in the Suzuki reaction under microwave irradiation.…”
mentioning
confidence: 99%